CORPORATE FINANCE AND CAPITAL BUDGETING DECISIONS - Jo’rayev Og’abek (Journal of Management and Economics, 2024)
This paper explores the significance of capital budgeting methods in corporate finance and their role in optimizing investment decisions to maximize shareholder value and enhance organizational performance. Through a comprehensive review of existing literature and empirical analysis, this study examines various capital budgeting techniques, including traditional methods like payback period and accounting rate of return, alongside modern approaches such as net present value (NPV), internal rate of return (IRR), and real options analysis. The research investigates the strengths, limitations, and practical implications of each method in different business contexts, considering factors such as risk, uncertainty, flexibility, and strategic alignment. Furthermore, the thesis evaluates the impact of technological advancements, regulatory changes, and market dynamics on the adoption and effectiveness of capital budgeting practices in contemporary corporate environments. The goal of this study is to improve financial decision-making processes and, eventually, the competitiveness and sustainable growth of contemporary businesses by illuminating the changing environment of capital budgeting and providing insights into best practices.